2002
DOI: 10.1002/pits.10042
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent suicide: An ecological approach

Abstract: Adolescent suicide, which has been ranked among the top 10 causes of death in the world, is an issue of increasing concern to school psychologists, educators, and parents. Here an ecological approach is proposed to enhance our understanding of how personal, interpersonal, and sociocultural factors contribute to the increased risk for suicide among adolescents. The ecological approach allows exploration of how adolescent suicide is determined by multiple factors related to the adolescent's personal history or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 108 publications
(118 reference statements)
3
57
0
6
Order By: Relevance
“…According to WHO hanging is the commonly used method of suicide in the developed [1,2] and developing countries [3]. The rates vary by country, socioeconomic and doi: 10.7243/2052-7896-4-2 the sociocultural status of the individual [4,5]. In this study, it was found that 0.34% of all autopsies performed in our institution were suicide deaths by hanging, there was no trend in the numbers of suicide deaths over the study of period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to WHO hanging is the commonly used method of suicide in the developed [1,2] and developing countries [3]. The rates vary by country, socioeconomic and doi: 10.7243/2052-7896-4-2 the sociocultural status of the individual [4,5]. In this study, it was found that 0.34% of all autopsies performed in our institution were suicide deaths by hanging, there was no trend in the numbers of suicide deaths over the study of period.…”
Section: Discussionmentioning
confidence: 99%
“…Suicide rates vary by countries, age, gender, marital status, ethnicity and socioeconomic status [4,5]. The ligature mark and its characteristics is the most relevant feature of hanging at autopsy, even in instances where the ligature material is not available during autopsy.…”
Section: Introductionmentioning
confidence: 99%
“…The association between school or academic stressors and suicide ideation among adolescents has been well documented in several research studies [4][5][6]. In school, adolescents often see themselves as being evaluated in terms of their academic performance, and the pressure to excel is an important measure of their success in school.…”
Section: Academic Stress and Suicidal Ideationmentioning
confidence: 99%
“…On the other hand, perhaps an unequal distribution of individual level variables not included in the model also account for the gender effect. For example, school-related problems such as being bullied, social exclusion, academic stress and academic achievement have all been found to be associated with suicidal ideation [30][31][32]. If such problems were unequally distributed according to gender composition in our sample, the inclusion of these variables could then remove or reduce the observed effect.…”
Section: Discussionmentioning
confidence: 99%